MO059COLEC10 AND 3MC SYNDROME: EXPANDING THE GENOTYPIC AND PHENOTYPIC SPECTRUM OF A VERY RARE DISEASE. (29th May 2021) - Migliorero, Martina; Kalantari, Silvia; Bracciamà, Valeria; Sorbini, Monica; Arruga, Francesca; Peruzzi, Licia; Biamino, Elisa; Amoroso, Antonio; Vaisitti, Tiziana; Deaglio, Silvia
Abstract: Background and Aims: 3MC syndrome is an autosomal recessive disorder encompassing a variable spectrum of abnormalities, among which facial dysmorphisms are characteristic. Mutations in genes which encode proteins involved in the lectin complement pathway MASP1, COLEC11 and recently COLEC10 have been identified in patients with 3MC syndrome, supporting their key role during human development. We present a 5 years old patient with typical 3MC phenotypic characteristics, including blepharophimosis, telecanthus, high arched eyebrows, fifth finger clinodactyly, horseshoe kidneys, diastasis recti, umbilical depression and sacral dimple. The diagnosis was confirmed by sequencing of COLEC10 gene and the putative pathogenic variant was functionally validated through in vitro assays. Method: COLEC10 gene was analyzed through Sanger sequencing. The secreted protein CL-L1 was investigated in the plasma of the patient and her parents by Western blot. The variant was introduced by a site-specific mutagenesis approach into a plasmid encoding wild-type human CL-L1. HeLa cells were then transfected with the mutated or wild-type plasmid and culture supernatant evaluated in a migration assay. Results: A homozygous frameshift variant c.807_810delCTGT p.(Cys270Serfs*33) was identified in the patient. Segregation studies confirmed the parents' carrier status for the variant. Functionally, the variant affects the chemo-attractive feature of CL-L1, as HeLa cells are less sensitive to the mutant protein compared to the WT one, resulting in a reduced migratory response. Conclusion: We report a patient affected by 3MC syndrome who, besides typical phenotypic signs, presents a patent ductus arteriosus, never described in association to COLEC10 before. The variant causative role was functionally confirmed in an in vitro assay, where the mutated protein failed to act as a chemo-attractant. We thus provide further evidence for CL-L1 role during embryonic development